Composición de Servicios en Ambientes de Computación Ubicua - Hermida, Victor A.; Suarez, Luis Javier; Rojas, Luis Antonio; Corrales, Juan Carlos; Caicedo, Oscar (Cadernos de Informática, 2011)
Ubiquitous computing has established itself as the next generation of communications, offering to users the capabilities of the networks at any time and place, in order to support their daily tasks. However, the deployment of services for ubiquitous computing environments requires several challenges, such as mobility, dynamism and heterogeneity. Generally, providing a service to users is relatively simple, but the demand for these is becoming more demanding, thereby inducing an innovative feature and therefore a high complexity and variability of services. To comply with the requirements of users, it is necessary to combine several services, which implies provide to ubiquitous environments of efficient mechanisms of discovery and composition. In this paper, we propose a service composition platform for ubiquitous computing environments, which considers the specification of the behavior of services, the user profile and context. Thus, it is possible to obtain a composite service, which apart from meeting the demand of the user, adjusts to your preferences and the context in which it is.